DETERMINATION OF PALMITIC ACID UPTAKE BY THE FAT BODY OF THE MADERA ROACH - Chang, Franklin; Esguerra, Nelson M.; Macion, Eduardo A. (Annals of Tropical Research, 1981)
Uptake of [1-14C] palmitic acid by the fat body of female adult Leucophaea maderae was measured in vitro. The fat body free fatty acid fraction showed the highest radioactivity, followed by triglyceride. The other lipid fractions showed low incorporation of label. The turnover of palmitate to triglyceride in the fat body of L. maderae appears to be slower than those reported for other insect species. A method of pre-labelling the fat body with a radioisotope was found satisfactory and reliable.